Atypical emotion recognition from bodies is associated with perceptual difficulties in healthy ageing - Chard, J; Edey, R; Yon, D; Murphy, J; Bird, G; Press, C (American Psychological Association, 2019)
A range of processes are required for recognizing others’ affective states. It is particularly important that we process the perceptual cues providing information about these states. These experiments tested the hypothesis that difficulties with affective state identification in older adults (OAs) arise, at least partly, from deficits in perceptual processing. To this end we presented “point light display” whole body stimuli to healthy OAs and comparison younger adults (YAs) in 3 signal detection experiments. We examined the ability of OAs to recognize visual bodily information—posture and kinematics—and whether impaired recognition of affective states can be explained by deficits in processing these cues. OAs exhibited reduced sensitivity to postural cues (Experiment 1) but not to kinematic cues (Experiment 2) in affectively neutral stimuli. Importantly, they also exhibited reduced sensitivity only to affective states conveyed predominantly through posture (Experiment 3) —that is, the cue they were impaired in perceiving. These findings highlight how affective state identification difficulties in OAs may arise from problems in perceptual processing and demonstrate more widely how it is essential to consider the contribution of perceptual processes to emotion recognition.